Colonization Screening Targeting Multidrug-Resistant Gram-Negative Pathogens Does Not Increase the Use of Carbapenems in Very Low Birth Weight Infants - Schöndorf, Dominik; Simon, Arne; Wagenpfeil, Gudrun; Gärtner, Barbara; Geipel, Martina; Zemlin, Michael; Schöndorf, Marika; Meyer, Sascha (Frontiers in Pediatrics, 2020)
Since 2012, a colonization screening (CoS) for multidrug-resistant Gram-negative bacteria (MRGN) in very low birth weight infants (VLWBI) was implemented in order to provide a basis for an effective empiric therapy of subsequent nosocomial infections (NI). According to antibiotic stewardship, carbapenems should be reserved for NI caused by MRGN or severe NI. We examined whether the CoS increased the first-line use of carbapenems. In this retrospective cohort analysis, we enrolled all VLBWI before (2009–2011) and after (2012–2014) the introduction of CoS (2012) at a tertiary university neonatal intensive care and neonatal intermediate care unit (NIMC) in Germany. Rectal swabs were used to detect MRGN colonization (on admission and weekly until discharge from the NIMC). The use of carbapenems was measured by days of therapy (DoT). To exclude the replacement of carbapenems by other antibiotics, antibiotic therapy for late-onset sepsis (LOS) was assessed by DoT and length of therapy (LoT). In 55/201 (27.4%) VLBWI, CoS detected MRGN colonization. Compared to the cohort prior to the introduction of CoS (n = 191), a significant decrease in LoT (p < 0.001) and total DoT (p < 0.001) was seen (n = 201). This was due to a significant decrease in LoT (p < 0.001) and total DoT (p < 0.001) in the birth weight category of 1,000–1,499 g. In these infants, DoT for carbapenems (p = 0.009) was significantly lower, possibly caused by a significant decline of LOS (25 episodes vs. 39 episodes, p = 0.025). Conversely, no significant differences in LoT and total DoT were seen in infants with a birth weight <500 g (p = 1.000; p = 0.758) and in infants weighing 500–999 g (p = 0.754; p = 0.794). DoT for carbapenems was not significantly different in the total cohort after the introduction of CoS (p = 0.341). Prolonged exposure to carbapenems (in terms of DoT) significantly postponed the first detection of MRGN colonization (p = 0.023). The introduction of CoS did not result in an increased use of carbapenems. Concomitant carbapenem treatment may reduce the sensitivity of CoS relying on rectal swabs.